The renormalization of neuronal dynamics can enhance temporal synchronization among synaptically coupled neurons - Jibril, Ghassan Omar; Guler, Marifi (IEEE, 2009)
Led by the presence of a multiple number of gates in an ion channel, it was recently predicted that the equations of motion for the neuronal dynamics acquire some renormalization terms which play a significant role in the dynamics for smaller membrane sizes [1]. In this study, we consider the resultant computational neuron model of the above approach, and investigate numerically how the renormalization corrections affect the temporal synchronization of the respective discharges of such electrically coupled two neurons. A major finding is that the presence of the renormalization terms can lead to faster synchronization.
International Joint Conference on Neural Networks -- JUN 14-19, 2009 -- Atlanta, GA
Keywords: Visual-Cortex; Networks; Model; Oscillations; Cat